Complex cerebral aneurysms: intra-luminal reconstruction using Pipeline flow-diverting stent and the obliteration mechanism. Issue 2 (April 2020) - Lv, Xianli; Jiang, Chuhan; Wu, Zhongxue; Jiang, Weijian; Wang, Guihuai
Objectives: Patients with complex cerebral aneurysms can now be treated intravascularly with the help of flow-diverting stents. The primary purpose of this article is to document the clinical and angiographic outcomes in 80 patients who were treated with the Pipeline flow-diverting stent (PFS; Medtronic, Dublin, Ireland) and the obliteration mechanism was discussed. Patients and methods: Between October 2015 and October 2019, 80 patients with 90 complex (undefined neck, large/giant, blood blister–like, and recurrent side-wall) cerebral aneurysms treated with the PFS were retrospectively reviewed. Forty-five patients were women and 35 were men, with a mean age of 52 years. Large or giant aneurysms were defined as 10 mm or larger and small aneurysms were defined as less than 10 mm at the largest diameter measured on angiogram. Results: Forty-one aneurysms (45.6%) were large or giant, 41 (45.6%) were small, four (4.4%) were recurrent side-wall aneurysms and four (4.4%) were blood blister–like aneurysms. In total, 87 PFSs were placed in 80 patients with 90 aneurysms. In six patients, coexisting proximal stenosis of parent artery was also covered with PFS without balloon angioplasty. Adjunct coils were placed in 31 aneurysms (34%). One patient died of intracerebral hematoma after thrombolysis. There was one intrastent occlusion at six-month follow-up without any symptoms. The morbidity and the mortality rate is 0% and 1.3% (95% confidence interval (CI), 0%–3.7%). Control angiography was available in 74 (92.5%) patients with 83 aneurysms, and the aneurysm occlusion rate was 98.8% (95% CI, 96.5%–100%) in 6 to 12 months. Conclusion: For wide-necked saccular, large/giant, blood blister–like aneurysms and recurrent side-wall aneurysms, PFS is a valid and safe treatment option.